Consumer Behavior in Green Marketing and its Influence on the Business Environment - Lakkhongkha, Kritsana (Journal of ASEAN PLUS Studies, 2022)
The fast-growing and fast-paced economy in today’s world has created tremendous growth for each country, including leading countries worldwide, such as Europe, America, and Asia. If looking at the competition in economic development in the ASEAN region, ASEAN has developed to compare the standards to support different technologies in the future as well. Measuring GDP growth by a country is a key standard that every country should plan for its development. Therefore, businesses must study consumer behavior trends best by using elements and understanding all aspects of the business environment, including economy, politics and law, technology, and environment. Today’s world must understand not only to develop and use the world’s resources but to consider the environment. That concept is the idea of environmental marketing and social responsibility, which is how entrepreneurs should treat society to maintain and create a better quality of life for people in that society to meet the needs of taking care of everything. The organization is one of the elements closely related to consumer groups. Therefore, it is necessary to begin analyzing consumer behavior in different contexts. The four business environments mentioned above must be understood sequentially and used qualitatively in the future.